Molecular Evolutionary Characteristics of the 2019 Novel Coronavirus (SARS-CoV-2) Contracted by Tunisian Citizens : Comparison and Relationship to Other Human and Animal Coronaviruses Based on Spike Glycoprotein-Coding Gene Sequences Analysis - Moncef, Boulila (International Journal of Coronaviruses, 2021)
In contributing to the initiative to address the COVID-19 pandemic and in order to enhance the knowledge on driving forces shaping the evolution of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) (isolated from Tunisian patients), a comparison in relation to other coronaviruses infecting humans (SARS-CoV-1, MERS-CoV, HCoV/229E, HCoV/NL63, HCoV/OC43, and HCoV/HKU1) as well as animals (SARS-CoVs in tiger, bats, civet, pangolin, bovine, and MERS-CoV in dromedary/camel), was conducted. In-depth analysis was carried out involving 115 sequences of spike glycoprotein-coding gene extracted from the international databases. Phylogeny inference allowed the reconstruction of a bifurcating tree where four distinct groups were delineated and at the same time, three animal accessions (SARS-CoV-2/tiger, MERS-CoV/camel, and SARS-CoV/bovine) shifted from the animal group and integrated the human coronaviruses clades. Nonetheless, in the presence of reticulate events such as recombination, networks described better the phylogenetic relationships rather than the classic dendrogram. Thus, networks were produced and identified four clusters containing sharply demarcated subgroups (eight subdivisions). Except networked phylogenies of SARS-CoV-1, SARS-CoV-2, and HCoV/HKU1, all the others showed edges and boxes illustrating the occurrence of incompatibilities related to the sequences of spike glycoprotein-coding gene. Thereby and consolidating this result, three methods (RDP package, GARD, and RECCO) were used to detect breakpoints in aligned sequences. Except the clades SARS-CoV-1 and SARS-CoV-2, all the remaining phylogenetic subdivisions were subject to recombination. Furthermore, the screening of selection pressure in all studied sequences by various statistics-based models of the HyPhy package, showed that, similarly, the lineages belonging to the clades SARS-CoV-1 and SARS-CoV-2 were not under selection. In contrast, all members of the remaining clades underwent, to different extents, adaptive selection as well as purifying selection.
Keywords: evolution; recombination; gene duplication; selective pressure; phylogeny; coronaviruses; SARS-CoV-2